A Fluorescent Polymer Coated Sensor Chip for Mercury Ion (Hg2+) Determination in Lake Water. Issue 36 (22nd September 2022) - Muhammad, Imran; Muhammad, Turghun; Hoji, Amina; Imerhasan, Mukhtar; Adnan,
Abstract: Novel dansyl chloride‐based fluorescent polymer‐coated chips (PCFCs) were designed and developed via polymerization of 2‐(5‐(dimethylamino) naphthalen‐1‐ylsulfonyloxy)ethyl methacrylate (DNS‐EMA) on the surface of a 3‐(trimethoxysilyl)propyl methacrylate (MPS) modified glass slide with a supporting membrane. The chemical linkage of DNS‐EMA on PCFC surface was verified by 1 H‐NMR, IR, and fluorescence measurements. Particularly, the optimized fluorescent polymer‐coated chip (PCFC6) in 1/1 (v/v) acetonitrile /water exhibited higher sensitivity toward Hg 2+ than the other tested metal ions at concentrations ranging from 1.66 μmol/L to 50.6 μmol/L with R 2 =0.9923. Interestingly, PCFC6 is water‐compatible, photostable and exhibits good selectivity to Hg 2+ even at low concentrations compared to other representative metal cations with 89.2‐109.9 % recoveries. Abstract : In this study, a methacrylate derivative of dansyl chloride were synthesized and applied to prepare a polymer coating, on a glass chip coupling with the micropore membrane, which has selective fluorescence response to Hg 2+ in a broad concentration range. The coating is water‐compatible and highly stable and can be used for the simple and accurate determination of Hg 2+ in water sample.